2008
DOI: 10.1039/b809438c
|View full text |Cite
|
Sign up to set email alerts
|

Melting and freezing of water in cylindrical silica nanopores

Abstract: Freezing and melting of H 2 O and D 2 O in the cylindrical pores of well-characterized MCM-41 silica materials (pore diameters from 2.5 to 4.4 nm) was studied by differential scanning calorimetry (DSC) and 1 H NMR cryoporometry. Well-resolved DSC melting and freezing peaks were obtained for pore diameters down to 3.0 nm, but not in 2.5 nm pores. The pore size dependence of the melting point depression DT m can be represented by the Gibbs-Thomson equation when the existence of a layer of nonfreezing water at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
404
4
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(454 citation statements)
references
References 55 publications
40
404
4
6
Order By: Relevance
“…3). A comparison of different techniques for determining porosity suggests that the k GT calibration constant is, as theoretically expected, dependent on pore geometry, but a full understanding of these factors is still being developed 7,17,18,19,20 . Measurements were made for the modified and non-modified materials using over-filled and partially-filled samples.…”
Section: Materials Characterisation: Nmr Cryoporometrymentioning
confidence: 90%
“…3). A comparison of different techniques for determining porosity suggests that the k GT calibration constant is, as theoretically expected, dependent on pore geometry, but a full understanding of these factors is still being developed 7,17,18,19,20 . Measurements were made for the modified and non-modified materials using over-filled and partially-filled samples.…”
Section: Materials Characterisation: Nmr Cryoporometrymentioning
confidence: 90%
“…Both theory 18 and experiments 19,20 showed that the melting temperature of ice is decreased by confinement. In particular, recent simulations showed that the equilibrium melting temperature of ice nanoparticles follows the Gibbs-Thomson equation 21,22 .…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, ice formation within the crystal apparently does not occur if the channels are smaller than about 30 Å . Pure water confined in hydrophilic silica materials (Dore, 2000) has also been reported not to form crystalline ice if the channel sizes are below 28 Å (Jahnert et al, 2008).…”
Section: Temperature-dependent Behaviour Of Protein Crystalsmentioning
confidence: 99%